Does Smart & Powerful CEO Contribute to the Performance of Technology Companies? - Karnoukhova, Elena; Stepanova Anastasia (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2019)
Innovative companies have become one of the major drivers of economy worldwide. According to various surveys, nearly 70% of the world’s most innovative companies in 2019 are US firms. However, academic studies have tended to focus on the influence of the top management team and the board of director’s on the firm performance, or the relationship between innovative activity and the CEO`s preferences. However, this overlooks the idea that the CEOs themselves can exert a significant influence on the performance of innovative companies. As such, we aim in this research paper to show which CEO characteristics could lead to a higher firm value. This research uses the generalised least squares model on a sample of 12,565 firm-year observations during the period 2004-2015. We used data for three innovative industries: (i) pharmaceuticals, biotechnology & life sciences, (ii) software and services, and (iii) technology hardware and equipment industries. Additionally, we hand-collected data from the CVs stored in the CIQ database. Finally, we provide examples to prove the validity of our tests. Our results indicate that educational background, tenure, and duality play crucial roles in explaining firm value. Our findings indicate that a CEO characteristics play crucial roles in explaining technology firm value and performance. We demonstrated that the founding CEO as well as a CEO with better education contributes more to firm performance. We found that the characteristics of a CEO can mitigate conflicts between different types of investors and their influence on firm performance. More specifically, the CEO-founder was found to add greatly to the performance of Software and Pharmaceutical companies. Furthermore, CEO influence seems to mitigate the conflict of interest with independent active institutional investors in the Hardware industry. The novelty of this paper resides in its specific answers to questions that are overlooked or taken for granted in broader studies on the same subject area. We emphasise the differences in ownership structure in high-tech and non-tech industries, and not only provide answers as to whether the vaunted ‘power’ of a chief executive is significant in increasing company value, but whether a highly educated CEO contributes more to innovations in the hi-tech sphere. The specificity of the empirical investigations concluded herein lends itself well to reference, and as such this paper provides opportunities for academics, students, professionals, and journalists in the business field to cite its conclusions in any number of media.